New Reconstruction Method for Needle Contrast Optimization in B-Mode Ultrasound Image by Extracting RF Signal Parameters in Frequency Domain - Hesty Susanti; Suprijanto Suprijanto; Deddy Kurniadi (Journal of Engineering and Technological Sciences, 2020)
Ultrasound-guided needle insertion has become standard in medical interventional procedures. Regardless of its advantages, it still has crucial problems related to needle visibility. Some technical factors affect the visibility with non-linear characteristic, i.e. frequency, insertion angle and depth. Here, backscattered signal parameters from measurement were compared to a simulation of a resonance scattering model. Raw radio frequency (RF) data were reconstructed with a new method to represent unique information on total backpropagation from the needle, which consists of non-resonance and resonance scattering components. The result suggests that reconstruction of the needle in B-mode images should be derived from the maximum power spectral density and the energy spectral density to optimize the contrast of the needle. In measurements with the center frequency at 1.87 MHz, the effect of resonance scattering on the total backpropagation around critical angles could be observed more clearly with this method than with standard reconstruction based on the signal envelope. The simulation showed that the fractional bandwidth of the spectrum of the backscattered pressure field centered at 1.87 MHz was relatively optimal at 40% to 100%. So that the simulation of the resonance scattering model can be used to predict the backscattered response from the needle, it must be able to confirm it to the real conditions of RF data with random characteristics. Therefore, extraction of the backscattered pressure field in a simulation with fractional bandwidth should be a concern.